2013
DOI: 10.1111/jpy.12108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological diversity of Narragansett Bay (RI, USA) Ulva (Ulvales, Chlorophyta) populations

Abstract: Macroalgal bloom-forming species occur in coastal systems worldwide. However, due to overlapping morphologies in some taxa, accurate taxonomic assessment and classification of these species can be quite challenging. We investigated the molecular and morphological characteristics of 153 specimens of bloom-forming Ulva located in and around Narragansett Bay, RI, USA. We analyzed sequences of the nuclear internal transcribed spacer 1 region (ITS1) and the chloroplast-encoded rbcL; based on the ITS1 data, we group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 63 publications
(143 reference statements)
1
36
0
1
Order By: Relevance
“…7) showed that the most closely species are U. lactuca and U. compressa (Guidone et al, 2013). However, U. fasciata (Pasad et al, 2009) is showed to be far from both U. lactuca and U. compressa.…”
Section: Data Inmentioning
confidence: 99%
“…7) showed that the most closely species are U. lactuca and U. compressa (Guidone et al, 2013). However, U. fasciata (Pasad et al, 2009) is showed to be far from both U. lactuca and U. compressa.…”
Section: Data Inmentioning
confidence: 99%
“…We conclude that the green tide-forming species is not U. prolifera, but U. linza. According to recent studies from New Zealand, Australia, and the USA, U. prolifera is monophyletic regardless of the genes (Heesch et al 2009, Kraft et al 2010, Guidone et al 2013, Kirkendale et al 2013. Several Ulva spp.…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 99%
“…1 was also described producing many branches mainly confined at the basal part (Ogawa et al 2013), and the branching manner coincided with U. partita. There are many field surveys of Ulva based on morphological and molecular phylogeny in Europe (Mareš et al 2011, Wolf et al 2012, Oceania (Kraft et al 2010, Kirkendale et al 2013, Micronesia (O Kelly et al 2010), North America (Guidone et al 2013), and Asia (Duan et al 2012, Bast et al 2014. However, U. partita has only been collected from the Japanese seashore.…”
Section: Discussionmentioning
confidence: 99%